H.I.V.E. Deadlock - Walden, Mark (Simon & Schuster Books for Young Readers, 2015)
Otto and Raven set out on a quest to locate the Glasshouse, where Anastasia Furan trains children as assassins, in an effort to rescue their friends. At the same time, Otto must elude the elite intelligence division known as The Artemis Section, which has been hunting Otto since he was expelled from H.I.V.E. three months ago.